A framework to guide dose & regimen strategy for clinical drug development. (25th September 2021) - Sander, Oliver; Magnusson, Baldur; Ludwig, Inga; Jullion, Astrid; Meille, Christophe; Lorand, Daniel; Bornkamp, Björn; Hinder, Markus; Kovacs, Steven J.; Looby, Michael
Abstract: Optimizing new drug therapies remains a challenge for clinical development, despite the use of ever more sophisticated quantitative methodologies. Although conceptually simple, the idea of finding the right treatment at the right dose for the right patient to ensure an appropriate balance of risks and benefits is challenging and requires a multidisciplinary approach. In this paper, we present a framework developed as a tool for organizing knowledge and facilitating collaboration in development teams.